FULMINANT CEREBRAL AIR EMBOLISM FOLLOWING ENDOVAC-THERAPY IN ESOPHAGEAL ANASTOMOTIC LEAKAGE – A RARE COMPLICATION. (23rd November 2019) - Herzberg, J; Jenner, R; Strate, T; Honarpisheh, H
Abstract: Aim: Anastomotic leakages after esophageal surgery is a major complication with an increased risk of mortality and an extended ICU and hospital stay. Surgical revisions or endoscopic interventions are standard procedures in treatment of such complications. The use of endoscopic endoluminal vacuum therapy (EVT) as introduced in the last years is considered a safe treatment. Background & Methods: We analyzed 78 patients who underwent a surgical resection of the esophagus from January 2015 until December 2018. We compared patients with endovac-therapy to patients without such endoscopic intervention. Length of stay in ICU and in hospital, patient's demographics and perioperative parameters were analyzed. Results: In our center, we performed 78 esophageal resections from January 2015 to December 2018. In 14.1% (11 patients) an anastomotic leakage appeared, in 10 patients (12.8% of all cases) we performed an endovac-therapy. In the endovac- group, the mean postoperative hospital stay was 39 days (± 18 days), which is a significant longer postoperative in-hospital time in compare to the other patients (mean 17 days, ±8 days, p=0, 004). Patients demographics and perioperative parameters were comparable in both groups. The postoperative 90-days mortality in the endovac-group was 20% (2 patients), in compare to a 90-days mortality rate of 4.4% in the group without an EVT. In one case we found the rare complication of an air embolism following an extended 35 days endovac-therapy. Endovac-therapy is a useful tool in the treatment of anastomotic leakage, although it is associated with a significantly prolonged hospital stay. Air embolism during endovac-therapy such as reported in this analysis, is a rare complication associated with endoscopic treatments. This is the first reported case of such an air embolism during endovac-therapy. Using carbon dioxide for endoscopic interventions might reduce the risk for air embolism, especially in high-risk-patients.